A comparative study assessing the wear behaviour of different ceramic die materials during superplastic forming: Eine vergleichende Studie zur Bewertung des Verschleißverhaltens unterschiedlicher keramischer Materialien für Formwerkzeuge während superplastischer Umformprozesse. Issue 10 (19th October 2017) - Gomez‐Gallegos, A. A.; Farrell, M.; Zuelli, N.; Staiano, A.
Abstract: Superplastic forming is an advanced manufacturing process where metallic sheets are heated to their superplastic region to be then blow formed within a die set. The process allows for the forming of complex parts but it is typically restricted to low volume production and high value pieces. Despite their brittle nature, ceramic dies are a developing technology for superplastic forming as they offer lower production costs and shorter lead times than conventional metallic dies, thus reducing process costs. This work presents a method to assess ceramic die wear by means of a novel test rig developed a at the Advance Forming Research Centre of the University of Strathclyde, Scotland, UK where the superplastic forming die‐part interaction can be replicated at laboratory scale. Controllable normal load tests at standard superplastic forming conditions on three different reinforced ceramic materials are carried out with a view to understanding their wear mechanisms and to ultimately identify methods to improve their wear resistance.